The importance of the distribution sector for exchange rate pass-through in a small open economy. A large scale macroeconometric modelling approach - Pål Boug; Ådne Cappelen; Torbjørn Eika (Statistics Norway, Research Department, 2013)
The degree of exchange rate pass-through to domestic goods prices has important implications for monetary policy in small open economies with floating exchange rates. Evidence indicates that pass-through is faster to import prices than to consumer prices. Price setting behaviour in the distribution sector is suggested as one important explanation. If distribution costs and trade margins are important price components of imported consumer goods, adjustment of import prices and consumer prices to exchange rate movements may differ. We present evidence on these issues for Norway by estimating a cointegrated VAR model for the pricing behaviour in the distribution sector, paying particular attention to exchange rate channels likely to operate through trade margins. Embedding this model into a large scale macroeconometric model of the Norwegian economy, which inter alia includes the pricing-to-market hypothesis and price-wage and wage-wage spirals between industries, we find exchange rate pass-through to be quite rapid to import prices and fairly slow to consumer prices. We show the importance of the pricing behaviour in the distribution sector in that trade margins act as cushions to exchange rate fluctuations, thereby delaying pass-through significantly to consumer prices. A forecasting exercise demonstrates that exchange rate pass-through to trade margins has not changed in the wake of the financial crises and the switch to inflation targeting. We also find significant inflationary effects of exchange rate changes even in the short run, an insight important for inflation targeting central banks.
Keywords: C51; C52; E31; F31; 330; Exchange rate pass-through; pricing behaviour; the distribution sector; econometric modelling and macroeconomic analysis.